A High Power Density Zero-Voltage-Switching Totem-Pole Power Factor Correction Converter - Tausif, Ali; Bakan, Ahmet Faruk; Dusmez, Serkan (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2024)
The power factor correction (PFC) circuit is an essential component in high-power supplies with nonlinear loads, occupying nearly half the size of a typical power supply. To minimize the size of passive components in PFC converters, the switching frequency must be increased to several hundred kHz, a challenge even when employing gallium nitride (GaN) devices under hard-switching conditions. This article proposes a new GaN-based totem-pole (TP) PFC converter integrated with a bidirectional soft-switching cell. Unlike critical-conduction-mode TP PFC circuit, the proposed converter operates in continuous-conduction-mode with simple control. Design considerations and optimization of soft-switching cell are discussed and verified with simulations. As a proof of concept, a two-phase interleaved version of the proposed converter rated at 3700Whas been designed. The designed prototype achieves a peak efficiency of 99.14% and surpasses the hardswitched GaN-based TP PFC converters in both power density and cost.
Keywords: Inductors; Field effect transistors; Topology; Switches; RLC circuits; Zero voltage switching; Gallium nitride; AC-DC converter; electric vehicle; on-board charger; power factor correction (PFC); totem-pole (TP); zero-voltage-switching (ZVS); BOOST CONVERTER; PERFORMANCE EVALUATION; RECTIFIER; BOUNDARY; DC; Engineering